2009
DOI: 10.1158/1055-9965.epi-09-0544
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in the Vitamin D Receptor Are Associated with Advanced Prostate Cancer at Diagnosis: Findings from the Prostate Testing for Cancer and Treatment Study and a Systematic Review

Abstract: Low levels of plasma vitamin D have been implicated as a possible risk factor for both prostate cancer incidence and advanced disease, and recent phase II trials suggest that vitamin D supplementation might delay progression of prostate cancer. Common polymorphisms in the vitamin D receptor (VDR) are associated with VDR activity and are therefore potentially useful proxies for assessing whether vitamin D is causally related to advanced prostate cancer. We genotyped five well-known VDR polymorphisms in 1,604 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 44 publications
8
35
1
Order By: Relevance
“…The actions of 1,25(OH) 2 D are mediated via the vitamin D receptor gene (VDR) [10], which is usually expressed in cells involved in calcium homeostasis, but it is also expressed in other cells, including the prostate [10]. A recent genetic association study and meta-analysis of 13 studies found an association between three VDR polymorphisms (BsmI, ApaI, and TaqI) and prostate cancer grade [48]: ApaI-a and BsmIb increased the risk of a high grade, TaqI-t was protective. These polymorphisms modulate the activity of the VDR and therefore may modulate a protective effect of 1,25(OH) 2 D with aggressive prostate cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The actions of 1,25(OH) 2 D are mediated via the vitamin D receptor gene (VDR) [10], which is usually expressed in cells involved in calcium homeostasis, but it is also expressed in other cells, including the prostate [10]. A recent genetic association study and meta-analysis of 13 studies found an association between three VDR polymorphisms (BsmI, ApaI, and TaqI) and prostate cancer grade [48]: ApaI-a and BsmIb increased the risk of a high grade, TaqI-t was protective. These polymorphisms modulate the activity of the VDR and therefore may modulate a protective effect of 1,25(OH) 2 D with aggressive prostate cancers.…”
Section: Discussionmentioning
confidence: 99%
“…[42] Furthermore, different kinds of chronic diseases and cancers seem to be associated with variations in the structure or functionality of the vitamin D receptor (VDR). [43][44][45][46] Vitamin D exerts its effects through interaction with its intracellular receptor (VDR), encoded by a gene located on chromosome 12; several singlenucleotide polymorphisms (SNPs) have been identified in the sequence of the gene encoding for VDR. The distribution of SNPs in this gene is different among human populations, and so a specific SNP that is common in one geographical or ethnic group may be less represented in another.…”
Section: Introductionmentioning
confidence: 99%
“…These men then underwent testing in PSA-testing clinics. From the results, 2000 PCa cases and 2000 controls were randomly selected to form one of the largest PCa case control studies in the world (15,16 ).…”
Section: Information About the Protect Studymentioning
confidence: 99%